Horsetails Are Ancient Polyploids: Evidence from Equisetum giganteum . Issue 6 (22nd May 2015) - Vanneste, Kevin; Sterck, Lieven; Myburg, Alexander Andrew; Van de Peer, Yves; Mizrachi, Eshchar
Abstract : An ancient polypoloidy event in horsetails during the late Cretaceous predates the divergence of today's extant species and may have contributed to the longevity of the genus Equisetum . Abstract: Horsetails represent an enigmatic clade within the land plants. Despite consisting only of one genus ( Equisetum ) that contains 15 species, they are thought to represent the oldest extant genus within the vascular plants dating back possibly as far as the Triassic. Horsetails have retained several ancient features and are also characterized by a particularly high chromosome count ( n = 108). Whole-genome duplications (WGDs ) have been uncovered in many angiosperm clades and have been associated with the success of angiosperms, both in terms of species richness and biomass dominance, but remain understudied in nonangiosperm clades. Here, we report unambiguous evidence of an ancient WGD in the fern linage, based on sequencing and de novo assembly of an expressed gene catalog (transcriptome) from the giant horsetail ( Equisetum giganteum ). We demonstrate that horsetails underwent an independent paleopolyploidy during the Late Cretaceous prior to the diversification of the genus but did not experience any recent polyploidizations that could account for their high chromosome number. We also discuss the specific retention of genes following the WGD and how this may be linked to their long-term survival.